Clarity PPM Fundamentals - Velpuri, Rama; Das, Arpit (Apress, 2011)
Clarity PPM Fundamentals provides an overview of CA Technologies' flagship Clarity PPM (short for project portfolio management). The book is organized by the Clarity modules independently, making it ideal for users whose needs are often defined by their current working module. It provides industry best practices for utilizing the Clarity product. With just a basic understanding of project management, you'll be able to understand all this book has to offer, from user to system administrator-unveiling hidden tricks and lessons from real implementation scenarios. The authors bring their extensive experience to bear to give you the best insights into making Clarity more powerful and useful for you. Foreword by David Dobson, EVP and Group Executive,  Customer Solutions Group, CA Technologies, Inc.